THE EFFECT OF SERVICE QUALITY ON STUDENT VISIT INTEREST TO THE LIBRARY OF UIN MAHMUD YUNUS BATUSANGKAR - Tri Yuliani (Jurnal Ilmu Perpustakaan dan Informasi Islam, 2022)
This study deals with the effect of service quality on the interest of students visiting the library of UIN Mahmud Yunus Batusangkar. The purpose of this study was to see whether there was a significant effect of service quality on student interest in visiting the library. This type of research is survey research with a quantitative approach. The instrument used to collect data is a closed questionnaire with a Likert scale. Alternative answers are “strongly agree, agree, undecided, disagree and strongly disagree”. Analysis of the data used is simple regression. The results of this study indicate that there is a significant effect between service quality on student visitation interest where the results of statistical calculations show that 27.4% and 72.6% of other factors. This means that the quality of service has a positive influence on the interest in student visits, which is 27.4%, then the interest in student visits is influenced by other factors.Keywords: Library Service Quality, Visiting Interests, Libraries